2014
DOI: 10.1021/ac501573g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Magnetic Bead Based Sample Preparation for Automated and High Throughput N-Glycan Analysis of Therapeutic Antibodies

Abstract: Full automation to enable high throughput N-glycosylation profiling and sequencing with good reproducibility is vital to fulfill the contemporary needs of the biopharmaceutical industry and requirements of national regulatory agencies. The most prevalently used glycoanalytical methods of capillary electrophoresis and hydrophilic interaction liquid chromatography, while very efficient, both necessitate extensive sample preparation and cleanup, including glycoprotein capture, N-glycan release, fluorescent deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 26 publications
1
84
0
Order By: Relevance
“…For these linkage position studies the substrate was labeled with a chromophore detected by fluorescence. The fluorescently conjugated oligosaccharides and glycans were labeled as previously described 34 with slight modifications. Glycan labeling was accomplished using 100 mM 8-aminopyrene-1,3,6-trisulfonic acid in 20% acetic acid for a reaction of 7 nmol glycan:250 nmol dye in a total reaction volume of 5 μL.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…For these linkage position studies the substrate was labeled with a chromophore detected by fluorescence. The fluorescently conjugated oligosaccharides and glycans were labeled as previously described 34 with slight modifications. Glycan labeling was accomplished using 100 mM 8-aminopyrene-1,3,6-trisulfonic acid in 20% acetic acid for a reaction of 7 nmol glycan:250 nmol dye in a total reaction volume of 5 μL.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Procedures reported in the literature apply comparable but not unified reaction conditions and reagent volumes for fluorescent sugar labeling [10], most of them suggesting overnight incubation at 37°C [29,33] or several hours of reaction times at higher temperatures (50°C) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, lectin‐based enrichment , hydrophilic interaction chromatography (HILIC) , porous graphitized carbon (PGC) and hydrazide based methods , are extensively used for the purification and enrichment of glycans. Over the past 5 years, several studies reported the use of a variety of materials to facilitate high‐throughput sample preparation .…”
Section: Advances In Glycan Purification Techniquesmentioning
confidence: 99%